Deciphering the role of alternative splicing as a potential regulator in fat-tail development of sheep: a comprehensive RNA-seq based study - Mohammad Reza Bakhtiarizadeh (Scientific Reports, 2024)
Abstract Although research on alternative splicing (AS) has been widely conducted in mammals, no study has investigated the splicing profiles of genes involved in fat-tail formation in sheep. Here, for the first time, a comprehensive study was designed to investigate the profile of AS events and their involvement in fat-tail development of sheep. In total, 45 RNA-Seq samples related to seven different studies, which have compared the fat-tailed vs thin-tailed sheep breeds, were analyzed. Two independent tools, rMATS and Whippet, along with a set of stringent filters were applied to identify differential AS (DAS) events between the breeds per each study. Only DAS events that were detected by both tools as well as in at least three datasets with the same ΔPSI trend (percent spliced in), were considered as the final high-confidence set of DAS genes. Final results revealed 130 DAS skipped exon events (69 negative and 61 positive ΔPSI) belonged to 124 genes. Functional enrichment analysis highlighted the importance of the genes in the underlying molecular mechanisms of fat metabolism. Moreover, protein–protein interaction network analysis revealed that DAS genes are significantly connected. Of DAS genes, five transcription factors were found that were enriched in the biological process associated with lipid metabolism like “Fat Cell Differentiation”. Further investigations of the findings along with a comprehensive literature review provided a reliable list of candidate genes that may potentially contribute to fat-tail formation including HSD11B1, SIRT2, STRN3 and TCF7L2. Based on the results, it can be stated that the AS patterns may have evolved, during the evolution of sheep breeds, as another layer of regulation to contribute to biological complexity by reprogramming the gene regulatory networks. This study provided the theoretical basis of the molecular mechanisms behind the sheep fat-tail development in terms of AS.